Formation of state archives of Belarus (1919–1922) - Hiarnovich, Tatsiana D. (Journal of the Belarusian State University. History, 2019)
The purpose of the article was to identify the activities that determined the formation of the state archives of Belarus. To achieve this goal, it was necessary to solve several problems: 1) identification of sources containing information on the collection of documentary complexes, the acquisition of documents from centralized state archives and the organization of the system of archival institutions; 2) identification of persons who participated in the creation of the Central Archive of the People’s Commissariat of Education of BSSR (Central Archive of BSSR); 3) identification of regulatory documents that preceded the first law on the archives of the BSSR. The relevance of the study is determined by the lack of development of the problems identified in the Belarusian archival studies. The article for the first time introduces into the scientific circulation sources about the acquisition of the first state archives, provides information about the funds of institutions, saved thanks to the efforts of D. I. Dovgyallo, N. P. Shklyaev, A. A. Savich, M. A. Vakhayev. The mechanism of transfer of archival complexes to the Central Archive of BSSR structure is revealed. Information is provided on the organizational, methodological foundations of the organization of the archival industry in the BSSR. As the predecessor institutions of the Central Archive of BSSR, the activities of the subdivision of the protection of monuments of antiquity and art of the art department of the People’s Commissariat of Education of the BSSR and the academic center of the People’s Commissariat of Education of the BSSR are considered. It is concluded that the activities of the People’s Commissariat of Education and the dedicated efforts of historians and archivists were also the basis for the creation of the National Archives of the Republic of Belarus, the National Historical Archives of Belarus. Based on the information revealed, it is proposed to clarify the history of archival institutions and revise the dates of their establishment. As a result of a comparative analysis of the normative acts on the archives of the RSFSR and the BSSR, a similarity of the wording of the original editions and theoretical guidelines of the first normative acts on the archives was revealed. It is concluded that the archives in the BSSR was determined under the influence of the regulations of the RSFSR. However, it is noted that the practical work on the preservation of archives, their unification into large complexes and the creation of a network of state archival institutions in the early 1920s in the BSSR was carried out exclusively by internal forces, on the basis of normative legal acts issued by republican government bodies.
Keywords: archival science; state archive; Central Archives of BSSR; laws on archives; BSSR